ANALISIS FLYPAPER EFEECT PADA BELANJA PEMERINTAH KOTA DAN KABUPATEN (Fokus Ekonomi, 2011)
This study aims to identify the occurrence of flypaper on the city and county governmentspending in Indonesia, in 2006-2008. In this case, the dependent variable used istheshopping area while the independent variable is revenue (PAD), the General AllocationFund (DAU), the Special Allocation Fund (DAK) and a dummy, to distinguish thecity /county Java and Outside Java. The sample in this study were 394 municipalities anddistricts in Indonesia with Data sources Relisasi Budget Report 2006-2008. This research usessoftware eviews 6. The analysis showed that in general does not occur flypaper on city andcounty government spending in Indonesia in 2006-2008. DAU and PAD respectively significantat 1% level, with a regression coefficient of0.601837 and 2.825710. Dummy variables indicatingthe occurrence of flypaper on the city / county in Java, while for municipalities and counties inOuter Java does not happen flypaper. This is because differences in potential revenues betweenJava and outside JavaKeywords: revenue, general allocation fund, the flypaper